Evaluation of Relationship between Water Absorption and Durability of Concrete Materials - S. P. Zhang; L. Zong (Advances in Materials Science and Engineering)
Environment has significant effects on the water absorption of concrete materials. This paper presents an experimental study of the influence of water absorption on the durability of concrete materials. A detailed analysis is also presented in order to establish useful relationship between them. Concrete specimens of different water absorption were prepared through different curing conditions, and results indicated that curing condition can significantly affect the surface water absorption. SEM photos also showed that different curing conditions caused different microstructure. After 28-days curing, compressive strength, permeability, sulfate attack, and chloride ion diffusion of concrete samples were investigated. As a result, both of surface sorptivity and internal sorptivity have no clear relationship with compressive strength. Results obtained also showed that only surface water absorption related to the performance of concrete including permeability, sulfate attack, and chloride ion diffusion. In addition, both impermeability and resistance to sulfate attack were linearly associated with surface sorptivity, and both correlation coefficients were not less than 0.9. Furthermore, chloride ion diffusion coefficient has exponent relation to surface water absorption with higher correlation coefficient. However, no apparent relationship was found between internal water absorption and durability like impermeability, resistance to sulfate attack, and chloride ion diffusion.